Anti–PD-1/PD-L1 antibodies in non-small cell lung cancer: the era of immunotherapy. Issue 1 (2nd January 2017) - Valecha, Gautam Kishore; Vennepureddy, Adarsh; Ibrahim, Uroosa; Safa, Firas; Samra, Bachar; Atallah, Jean Paul
ABSTRACT: Introduction: Advanced non-small cell lung cancer (NSCLC) has been conventionally treated with cytotoxic chemotherapy with short-lived responses and significant toxicities. Monoclonal antibodies to programmed death-1 receptor (PD-1) and programmed death ligand 1 (PD-L1) have shown tremendous promise in the treatment of advanced NSCLC in various clinical trials. Areas covered: In this article, we will review the outcomes of various trials of anti-PD-1/anti-PD-L1 antibodies in the treatment of NSCLC. We will also discuss their mechanism of action and toxicities. Expert commentary: Anti-PD-1/PD-L1 antibodies offer several advantages including significant antitumor activity, induction of long lasting responses, and favorable safety profile. Several trials are now being conducted to evaluate their efficacy as first line agents as well as in combination with other agents. More research is also needed to identify other biomarkers, in addition to PD-L1 expression, that could more reliably predict response to these drugs, and aid in better patient selection.